Development of trade-economic cooperation of the Republic of Kazakhstan and Turkey in the light of implementation of the program a new silk road - Кренгауз, И. Н. (Journal of Oriental Studies, 2018)
The aim of the research – identification of the major challenges and trends in developing the economic cooperation between Kazakhstan and Turkey in light of the implementation of the program «New Silk Road».Methodology – general scientific principles of knowledge of the economic phenomena were used in the research process: the dialectical, concrete historical, morphological systematic, etc. Approaches which allow us to review the phenomena being studied and their development processes, to identify contradictions, and to relate the essential characteristics and forms of their manifestation, were used along with the long established techniques, such as analysis, synthesis, deduction and induction, and methods of economic and statistical analysis. Originality/value – based on the method worked out by the author, an analysis of the dynamics of cooperation between Kazakhstan and Turkey are carried out on two main indicators of integration – mutual trade and mutual investments for fifteen years according to the statistics from the international organization for trade marketing. Recommendations are made to try and bring to perfection the bilateral cooperation between Kazakhstan and Turkey in light of the implementation of the program «New Silk Road». Conclusions – the research has revealed, therefore, that the current commodity composition of import in Kazakhstan reflects the unrealized potential for strengthening linkages between the country and countries in the New Silk Road Economic Belt. Inter-linkages, particularly with Turkey, as the two countries may work hand in hand towards the development regional machine-building and chemical complexes, the food processing industry and agriculture in general. With a view to strengthen the cooperation, in our opinion, it is necessary to go in the direction of cross-national cooperation, to orient the economy to develop in an innovative way. Furthermore, all the costs on building infrastructures necessary for effective functioning of the business must be taken, from our own point of view, by the so-called inter-state consortia. A significant potential to increase exports could give the development of the service sector. A move to enhance the government policy on stimulating the attraction of direct foreign investment not only in the manufacturing sector of the economy, but also to the financing of the interstate breakthrough innovative projects that will enable countries in the New Silk Road Economic Belt to take position on the market of finished products remains appropriate.